Neighborhood-prime labeling of some product graphs - Patel, S.K.; Shrimali, N.P. (Algebra and Discrete Mathematics, 2018)
We have introduced the concept of neighborhood-prime labeling and investigated it for paths, cycles, wheels and union of such graphs earlier. In this paper, we construct neighborhood-prime labelings for graphs that are cartesian or tensor product of two paths.